Clear English pronunciation a practical guide - Smakman, Dick 1970- (Routledge, 2020)
"Clear English Pronunciation provides students with the tools to effectively communicate in English without centering solely on native-speaker pronunciation models. The focus of the book is on individual pronunciation targets rather than a one-size-fits-all approach. Divided into four sections, each featuring detailed articulatory explanations, sample sentences and recordings to help learners improve their pronunciation, this book: introduces the phenomenon of pronunciation as part of a broader communicative realm; explains and demonstrates the melody and rhythm of understandable and natural English pronunciation; supports students in identifying and practicing their own pronunciation issues. Supported by an interactive companion website which features recordings and expanded explanations of key topics, Clear English Pronunciation is an essential textbook for international learners of English who want to improve their pronunciation skills in diverse social settings"--
Description based on online resource; title from digital title page (viewed on March 12, 2020)
Keywords: English language / Pronunciation; English language / Pronunciation by foreign speakers; English language / Phonology; English language / Spoken English